Symbiont‐specific responses to environmental cues in a threesome lichen symbiosis. Issue 5 (3rd January 2023) - Almer, Jasmin; Resl, Philipp; Gudmundsson, Hörður; Warshan, Denis; Andrésson, Ólafur S.; Werth, Silke
Abstract: Photosymbiodemes are a special case of lichen symbiosis where one lichenized fungus engages in symbiosis with two different photosynthetic partners, a cyanobacterium and a green alga, to develop two distinctly looking photomorphs. We compared gene expression of thallus sectors of the photosymbiodeme‐forming lichen Peltigera britannica containing cyanobacterial photobionts with thallus sectors with both green algal and cyanobacterial photobionts and investigated differential gene expression at different temperatures representing mild and putatively stressful conditions. First, we quantified photobiont‐mediated differences in fungal gene expression. Second, because of known ecological differences between photomorphs, we investigated symbiont‐specific responses in gene expression to temperature increases. Photobiont‐mediated differences in fungal gene expression could be identified, with upregulation of distinct biological processes in the different morphs, showing that interaction with specific symbiosis partners profoundly impacts fungal gene expression. Furthermore, high temperatures expectedly led to an upregulation of genes involved in heat shock responses in all organisms in whole transcriptome data and to an increased expression of genes involved in photosynthesis in both photobiont types at 15 and 25°C. The fungus and the cyanobacteria exhibited thermal stress responses already at 15°C, the green algae mainly at 25°C, demonstrating symbiont‐specific responses to environmental cues and symbiont‐specific ecological optima.